Congestive Heart Failure Following COVID-19 Vaccination - Yendrapalli, Usha; Chen, Henry J.; Punnanithinont, Natdanai; Elawad, Ahmed (Cardiology and Cardiovascular Medicine, 2022)
Myocardial injury following vaccination, particularly coronavirus disease 2019 (COVID-19), smallpox, influenza, hepatitis B has been documented as a rare side effect. In this report, we present a case of congestive heart failure that developed in a healthy male following the BNT162b2 mRNA-Pfizer-BioNTech vaccine. A 47-year-old male developed shortness of breath 5 days after receiving the second dose of Pfizer vaccine presented multiple times to urgent care, primary care physician office, and emergency room and had been misdiagnosed with bronchitis and allergies. Eventually after several weeks he was admitted due to worsening dyspnea and got echocardiography which showed an EF of 15% and cardiac catheterization did not reveal significant obstruction of coronary arteries. He was successfully diuresed and was discharged home symptom-free. We aim to increase awareness of this rare side effect of the COVID mRNA vaccination so that it can be recognized early and treated promptly to avoid complications.